Hubungan Pola Asuh Orang Tua dan Kecemasan Anak Berhadapan Hukum di Lembaga Pembinaan Khusus Anak - Lydia Suliyanto Wijaya; Billy Nugroho; Tia Melandri; Dzikrina Istifa Ramadhani; Naomi Soetikno (Universitas Andalas, 2024)
The number of children in conflict with the law continues to increase from year to year. It was noted that in 2020 and 2021 there were 1,700 children and increased to 1,800 children in 2022. Children in conflict with the law can feel negative feelings, can feel negative feelings, in the form of anxiety and one of the factors that influence it is parenting. One of the factors that influence anxiety is parenting. Children in conflict with the law in their detention period have very limited contact with their parents. This study aims to look at the relationship of parenting on children in conflict with the law anxiety in correctional institutions. The research method used was purposive sampling, with a total of 52 participants. The measuring instruments used in this study consisted of two, namely the Depression Anxiety Stress Scale (DASS-21) and Parenting Scale. The results of this study showed that paternal permissive parenting was associated with children in conflict with the law anxiety while other paternal types of parenting were not. Furthermore, maternal parenting did not have a relationship with children in conflict with the law anxiety. This study highlights the importance of social support in correctional institutions to reduce the anxiety of children in conflict with the law and the need to educate parents about the impact of permissive parenting in supporting children's development